Introduction to international disaster management - Coppola, Damon P. (Butterworth-Heinemann, 2015)
This edition provides practitioners and students with a comprehensive understanding of the disaster management profession by utilizing a global perspective and including different sources of risk and vulnerability, systems that exist to manage hazard risk and the many different stakeholders involved. It examines the impact of many recent large-scale and catastrophic disaster events on countries and communities, as well as their influence on disaster risk reduction efforts worldwide. It also expands coverage of small-island developing states (SIDS) and explores the achievements of the United Nations Hyogo Framework for Action (2005-2015) and the priorities for action in the Post-2015 Framework for Disaster Risk Reduction currently under development. It provides updated statistics on disaster frequency and impact and presents information on multilateral emergency management agreements as well as profiles of important NGOs and international organizations. --